Kindergarten Teachers' Perceptions of Ecological Education Programs in Preschoolers - A Focus Group Approach - Andreea A. Marin; Alina S. Rusu (Babes-Bolyai University, 2023)
The purpose of ecological education (EE), in addition to promoting understanding of environmental issues and the motivation to deal with them, is to ensure that preschoolers understand that humans are part of the biosphere and that they have the ability to impact its functionality in various levels. Kindergarten teachers are important agents of change in terms of creating opportunities for children to experience and internalise values based on ecological education. The objective of this study is to investigate teachers' perceptions of the EE programs in preschoolers, i.e. activities focusing on the direction of developing environmentally friendly behaviors and attitudes in children. Focus group methodological approach was used in order to collect the reflections of five kindergarten teachers in Romania. The focus group was guided by specific questions. Group members were convened online, being informed that the entire meeting would be recorded and that the data would be confidential and used strictly for research purposes Following the thematic qualitative analysis of the transcript, the idenitified themes indicate that teachers expressed openness and readiness to implement ecological educational activities in their own classes with the aim of fostering a friendly behavior of children with the environment.